The Performance of Agricultural Extension Workers in Utilizing Cyber Extension in Malang Raya Region - Sabir Sabir; Sugiyanto Sugiyanto; Keppi Sukesi; Yayuk Yuliati (Publisher of Widyagama University of Malang (UWG Press), 2018)
Cyber extension is a system of agricultural extension information through the internet media to support the provision of extension materials and agricultural information for extension workers. The existence of cyber extension is expected to support the performance of agricultural extension workers. This study aims to describe the implementation of cyber extension, describe the extension worker in the utilization of cyber extension and formulate the improvement efforts of extension worker in cyber extension in Malang Raya area. The research method used a combination of quantitative and qualitative (concurrent mixed method). This study revealed that three regions did not have administrator or manager of cyber extension. In addition, the results of descriptive analysis showed that the performance of agricultural extension-based cyber extension in Malang Raya region is still very low. Several efforts that can be taken by the government are to facilitate the technical implementation unit of extension with cyber extension equipment, the provision of financing budget and the socialization of cyber extension utilization to the extension worker.JEL Classification: D80, Q16, Q18